Effect of Hands on Instructional Activities on Students Retention of Mathematics Concepts Among Senior Secondary Schools in Jalingo Metropolis - Yukwa, Bernard Alpha (Darul Yasin Al Sys, 2025)
This study focuses the effect of Hands on Instructional Activities in Students’ Retention of Mathematics concepts in Jalingo Metropolis. The area of the study was carried out in Jalingo local government area. The research design used for the study was Quasi- experimental design. The population for the study was made up of all the senior secondary school Students. A total population of 5,236 students made up the study out of which 2,431 were female and 2,805 were male. A sample of thirty (30) students were considered for the findings from Government College Jalingo. Simple random sampling was used for the study. The instrument used for the research findings was an Achievement test for data collection and lesson plan was used for instruction. Data was obtained through administering the instruction and Achievement test to the students of the selected school. The researcher used t-test for the results. At 5 % level of significance, the test of hypothesis was carried out to compare the results of the two groups. Findings revealed that the male students in the experimental group were reported a lower score than male of the control group and that the performance of female students in the experimental group perform higher than the female student in control group. Findings further revealed that there is no significance differences in gender performance of students taught using hands on instructional activities on their retention level in learning of mathematics concepts. It was recommended in this study that Mathematics teachers at the basic education level should always make available instructional aids in their classroom, it should cover the content of each steps covered on the lesson plan to enable full participation of the learners and Gender equality should play a significant role in their classroom. No student should be assessed based on teacher’s favorite of the students’ gender.